The Important Role of Shipboard Maritime Correspondents for Officers - Sibali, Alwi; Kurniawaty; Ansar (Cendekiawan Indonesia Timur, 2024)
This paper examines the significant role of shipboard maritime correspondents in assisting officers with the communication and documentation processes essential to vessel operations. Maritime correspondents serve as key intermediaries, ensuring effective communication between ship officers, crew, shipping companies, port authorities, and regulatory bodies. Their duties go beyond routine administrative work; they manage critical documentation, including voyage reports, cargo manifests, and compliance records, while also maintaining efficient communication channels for safety and operational needs. The increasing complexity of global maritime operations, coupled with the rise of digital communication systems, has further highlighted the importance of this role. Shipboard maritime correspondents ensure that officers can concentrate on core responsibilities such as navigation, safety management, and ship handling without being overwhelmed by correspondence duties. This study underscores the essential skills required for the role, including knowledge of maritime law, technical terminology, and proficiency in modern communication tools. It also explores how correspondents contribute to reducing miscommunication risks and improving the overall operational efficiency and safety of maritime activities. By recognizing the value of these professionals, the maritime industry can better appreciate their impact on the seamless functioning of global shipping.